Codelivery of Anticancer Drug and Photosensitizer by PEGylated Graphene Oxide and Cell Penetrating Peptide Enhanced Tumor-Suppressing Effect on Osteosarcoma - Zhang, Xinliang; Gao, Wenjie; Chen, Jijun; Guo, Yunshan; Zhu, Jinwen; Meng, Yibin (Frontiers in Molecular Biosciences, 2021)
Objective: Graphene oxide (GO) has been widely used for various biological and biomedical applications due to its unique physiochemical properties. This study aimed to investigate the effects of cell penetrating peptide (CPP) modified and polyethylene glycol (PEG)-grafted GO (pGO) loaded with photosensitive agent 2-(1-hexyloxyethyl)-2-devinyl Pyropheophorbide -alpha (HPPH) and Epirubicin (EPI) (HPPH/EPI/CPP-pGO) on tumor growth in osteosarcoma. Methods: The HPPH/EPI/CPP-pGO were prepared, and then in vitro drug release assay was conducted. The detection of singlet oxygen (1O2) and cellular uptake of HPPH was performed as well. Next, the effects of control (saline solution), CPP-pGO, EPI, HPPH, HPPH/CPP-pGO, EPI/CPP-pGO, HPPH/EPI/pGO and HPPH/EPI/CPP-pGO were evaluated by MTT assay, colony-forming assay, and cell apoptosis assay in MG-67 cells. Furthermore, the anti-tumor effects of HPPH/EPI/CPP-pGO on osteosarcoma xenograft mice were unraveled. Results: The 1O2 generation and cellular uptake of HPPH were significantly increased after CPP and pGO modification compared with free HPPH. In addition, compared with control cells, CPP-pGO treatment had low cytotoxicity in MG-67 cells. Compared with free HPPH or EPI, HPPH/CPP-pGO or EPI/CPP-pGO treatment significantly inhibited cell viability and colony forming number, as well as induced cell apoptosis. HPPH/EPI-pGO treatment showed stronger inhibition effects on MG-67 cells than HPPH/CPP-pGO or EPI/CPP-pGO, and HPPH/EPI/CPP-pGO was the most effective one. Similarly, in vivo experiments revealed that compared with control group, the tumor size and weight of osteosarcoma xenograft mice were obviously decreased after free HPPH or EPI treatment, and which were further reduced in other groups, especially in HPPH/EPI/CPP-pGO group. Conclusions: HPPH/EPI/CPP-pGO had a superior tumor-inhibiting effects in vitro and in vivo on osteosarcoma.